2021
DOI: 10.1016/j.pcd.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of routine diabetes care during COVID-19 era: A systematic search and narrative review

Abstract: Background The world is facing the current COVID-19 pandemic. The pandemic response is affecting routine health care provision all over the world. We aimed to review the relevant literature and highlight challenges in the provision of routine care for patients with diabetes during the COVID-19 outbreak. Methods We systematically searched PubMed, ScienceDirect, and Embase databases up till August 13, 2020 and retrieved relevant articles published on difficulties on routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 30 publications
(57 reference statements)
1
43
0
Order By: Relevance
“…The broader living context for people with diabetes in the UAE, and unlike other countries, might have facilitated self-management including lack of disruption in the pharmaceutical supply chain, no difficulties in procurement of diabetes medications, no restriction in food supplies, initiatives to support patients such as the delivery of prescribed medicines to people’s homes, and the availability of telemedicine [13] , [29] . As expected and in line with similar studies in other countries, adherence to exercise was the lowest during the pandemic that mandated lockdowns and closure of sport facilities [23] , [26] , [30] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The broader living context for people with diabetes in the UAE, and unlike other countries, might have facilitated self-management including lack of disruption in the pharmaceutical supply chain, no difficulties in procurement of diabetes medications, no restriction in food supplies, initiatives to support patients such as the delivery of prescribed medicines to people’s homes, and the availability of telemedicine [13] , [29] . As expected and in line with similar studies in other countries, adherence to exercise was the lowest during the pandemic that mandated lockdowns and closure of sport facilities [23] , [26] , [30] .…”
Section: Discussionsupporting
confidence: 90%
“…Our study provided broad insight into the everyday management and challenges of diabetes during the COVID-19 pandemic among Arabic-speaking people with type 2 diabetes in the UAE. Although the pandemic has adversely affected the well-being of many people with diabetes worldwide [9] , [10] , [23] , [24] , [25] , [26] , participants in this study did not report high diabetes-related distress nor did they experience worsening glycemic control. We postulate that intensification of therapy could have masked a potential worsening in glycemic control.…”
Section: Discussionmentioning
confidence: 73%
“…COVID-19 is a global health crisis, challenging the preparedness of health systems’ all over the world as well as the ability to cope with and sustain a pandemic response [ 3 ]. It has been clinically observed that diabetes was associated with an increased risk of developing severe forms of COVID-19 such as ARDS (acute respiratory distress syndrome) and increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…This chronic condition increases the risk of disabling and life-threatening complications from micro- and macro-vascular diseases [ 3 ]. Which is important to understand the special aspects of COVID-19 infection in people with this underlying comorbidity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has placed a noticeable effect on patients with chronic diseases who require long-term care, of which diabetes was reported to be most influenced by the reduction in healthcare resources in the pandemic [4]. Besides the difficulties of shortage in medical staff and standard outpatient clinics, delayed care seeking, limited self-care practice, transportation inconveniency and unidentified adverse events all contributed to the major challenges of traditional diabetes care in the COVID-19 era [5].…”
Section: Introductionmentioning
confidence: 99%